1963
DOI: 10.1172/jci104789
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Factor Viii (Antihemophilic Globulin) and Factor Ix (Plasma Thromboplastin Component) in Normal Humans*

Abstract: There is much evidence favoring the concept of coagulation as a continuous process in the normal subject. In order to learn more about the dynamics of this process, we have been studying the survival of physiological amounts of the various clotting factors in the normal subject. With the development of isotope labeling, it has for the first time become possible to carry out such studies. We (1-3) and others (1-10) have applied this technique to studies of platelet and fibrinogen turnover. These studies were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Relatively few observations were possible in four of the patients; in these, the first posttransfusion specimen was obtained between 15 and 30 min after completion of the infusions and the half-life was calculated from the peak values observed. In patient D, a specimen was obtained immediately following administration of the concentrate and a second 25 min later; in this patient, a biphasic decline in antigen levels was observed as has been suggested by other studies (9). The half-life in this patient therefore was calculated from the determinations made 25 min after completion of treatment (that is, at the time when the first postinfusion specimens were obtained from the other patients).…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…Relatively few observations were possible in four of the patients; in these, the first posttransfusion specimen was obtained between 15 and 30 min after completion of the infusions and the half-life was calculated from the peak values observed. In patient D, a specimen was obtained immediately following administration of the concentrate and a second 25 min later; in this patient, a biphasic decline in antigen levels was observed as has been suggested by other studies (9). The half-life in this patient therefore was calculated from the determinations made 25 min after completion of treatment (that is, at the time when the first postinfusion specimens were obtained from the other patients).…”
Section: Methodsmentioning
confidence: 61%
“…Only one previous study with which we are familiar employed an immunological technique to determine the halflife of infused AHF. Information not available at the time of that study now raises questions as to the specificity of the antibody employed, but nevertheless Adelson and his colleagues, using such a technique, also reported a half-life of AHF considerably longer than that 12 hr usually observed when clot-promoting activity assays alone are employed (9).…”
Section: Resultsmentioning
confidence: 99%
“…0. 18 A multiple comparion test (37) was used. Our hypotheses are by no means satisfying, but it is interesting to note that in another situation, Fabry's disease, the transfusion of normal plasma is followed by a rise in the concentration of an enzyme, ceramide trihexosidase, present in diminished amounts in this disorder (12).…”
Section: Discussionmentioning
confidence: 99%
“…Using physicochemical methods, Hershgold, Silverman, Davison, and Janszen (13) and Barrow and Graham (14) reported the isolation of material similar to AHF from hemophilic plasma. Heterologous antisera directed against relatively crude AHF preparations have been prepared by several investigators (15)(16)(17)(18)(19)(20). Utilizing such heterologous antisera, Shanberge and Gore (16), Berglund (17), and Piper and Schreier (19) demonstrated that the plasma of hemophiliacs neutralized the capacity of the antisera to inactivate AHF.…”
Section: Discussionmentioning
confidence: 99%
“…More extensive studies have since yielded information which, though in itially contradictory, now appears to support these original conclusions. Several investigators utilizing heterologous antiserum either were not able to dem onstrate these Factor VIII antigens in hemophilic plasma (8)(9)(10) or could find them only in a small minority of cases, usually those retainin g some procoagulant activity (11,12). Additional studies with antibodies having specificity for apparently differ ent intramolecular sites have demonstrated antigenic expressions of Factor VIII in almost all hemophilic plasmas, including those without detectable Factor VIII procoagulant activity and lacking functional site-associated antigens (13)(14)(15).…”
Section: Classic Hemophilia: a Defective Factor VIII Moleculementioning
confidence: 99%